Influences of food hardness on the particle size distribution of food boluses - Chen, Jianshe; Khandelwal, Niharika; Liu, Zhenyu; Funami, Takahiro (Archives of oral biology, 2013)
Bolus swallowing or deglutition is a vital oral action which transports orally processed food from the oral cavity to the stomach for further digestion. Swallowing is routine to most health individuals, but it could be highly hazardous to many elderly and dysphagia patients. In order to provide proper food for safe consumption by these disadvantaged populations, a fundamental understanding of how bolus swallowing is triggered and is based on what criteria is urgently needed. Main objective of this work was to understand the physical properties of food boluses, in particular the bolus particle size distribution in relation to the hardness of the food. Food samples were chewed in free style by subjects and boluses were expectorated when subjects felt they were ready to be swallowed. Altogether seven different types of food were used and 10 health subjects participated in this study. Bolus particles were carefully washed and spread out on a flat surface. Images of bolus particles were taken using a digital camera and analysed using Image Pro Plus software for particle size quantification. Food hardness was measured using a Texture Analyser by a puncture test. It was observed that bolus particle size decreased with the increase of food hardness. The correlation between the two properties can be described by a power-law relationship. This relationship was also found applicable to literature results reported by Peyron et al. and Jalabert-Malbos et al. Food hardness has a direct influence on its bolus particle size. The harder the food, the smaller the bolus particle size.